2016
DOI: 10.1038/srep36112
|View full text |Cite
|
Sign up to set email alerts
|

Novel Toll-like receptor-4 antagonist (+)-naloxone protects mice from inflammation-induced preterm birth

Abstract: Toll-like receptor 4 (TLR4) activation by bacterial infection, or by sterile inflammatory insult is a primary trigger of spontaneous preterm birth. Here we utilize mouse models to investigate the efficacy of a novel small molecule TLR4 antagonist, (+)-naloxone, the non-opioid isomer of the opioid receptor antagonist (−)-naloxone, in infection-associated preterm birth. Treatment with (+)-naloxone prevented preterm delivery and alleviated fetal demise in utero elicited by i.p. LPS administration in late gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 67 publications
3
51
0
1
Order By: Relevance
“…Well before 37 weeks of pregnancy, premature newborns can be a fraction of the weight and size of babies at term. The same is true for pups from mice induced to give birth preterm about days 15-17 of pregnancy vs. those at term on days 19-20 postbreeding (106,134). These observations about newborn size difference, irrespective of etiology for preterm labor, raise the possibility that inflammatory processes that drive ripening, compliance, and dilation may not necessarily need to be the same in preterm vs. term birth.…”
Section: Immunobiologic Perspective On Cervix Remodeling With Pretermmentioning
confidence: 84%
“…Well before 37 weeks of pregnancy, premature newborns can be a fraction of the weight and size of babies at term. The same is true for pups from mice induced to give birth preterm about days 15-17 of pregnancy vs. those at term on days 19-20 postbreeding (106,134). These observations about newborn size difference, irrespective of etiology for preterm labor, raise the possibility that inflammatory processes that drive ripening, compliance, and dilation may not necessarily need to be the same in preterm vs. term birth.…”
Section: Immunobiologic Perspective On Cervix Remodeling With Pretermmentioning
confidence: 84%
“…Inflammatory response leads to leukocyte infiltration, edema, vascular dilatation and release of excess inflammatory cytokines, resulting in detachment of connective tissue, formation of periodontal pocket and resorption of alveolar bone and ultimately tooth loss [18,19]. Previous investigations revealed that some early-response pro-inflammatory cytokines such as TNF-α, IL-6 and IL-1β are released in response to external stimuli or tissue injury [20]. However, excessive levels of these pro-inflammatory cytokines activate inflammatory reaction cascades, thereby aggravating the inflammatory response that results in periodontitis [18,20].…”
Section: Gingivalis P Intermedius a Actinomycetemcomitans F Nucmentioning
confidence: 99%
“…Previous investigations revealed that some early-response pro-inflammatory cytokines such as TNF-α, IL-6 and IL-1β are released in response to external stimuli or tissue injury [20]. However, excessive levels of these pro-inflammatory cytokines activate inflammatory reaction cascades, thereby aggravating the inflammatory response that results in periodontitis [18,20]. It is also known that excess release of these pro-inflammatory cytokines induce damage to bone tissues of the teeth [2,21,22].…”
Section: Gingivalis P Intermedius a Actinomycetemcomitans F Nucmentioning
confidence: 99%
“…Bacterial structures called pathogen‐associated molecular patterns (PAMPs) are recognized by pattern recognition receptors (PRRs) that exist in monocytes/macrophages, granulocytes, and dendritic cells, as well as certain non‐immune cells that lie at potential entry sites of pathogens . In experimental settings, PTD can be caused by the injection of bacterial lipopolysaccharide (LPS); LPS is recognized by one well‐studied PRR namely Toll‐like receptor (TLR)‐4 that recognizes Gram‐negative bacteria whose contribution in the pathogenesis of PTD has been deciphered . C‐type lectin receptors (CLRs) are another type of PRRs.…”
Section: Introductionmentioning
confidence: 99%